Socio-Cultural Impacts of Educational Tourism on the Residents of Famagusta - Rezapouraghdam, Hamed (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2013)
Apart from palpable and potent effects of the tourism on the economy and the physical environment, it can be contributed to the socio-cultural vicissitudes in the host communities. Educational tourism as one of the most influential segments of tourism both from the economic and socio-cultural standpoints has an accelerating pace of development in the whole globe. Previous studies mostly have focused on the economic impacts of educational tourism and slightly have gone through the social and cultural impacts of the issue whereas; the present study aimed at scrutinizing the feasible social and cultural efficacies of educational tourism on the indigenous habitants of Famagusta city located in Northern Cyprus. In order to collect the related data, the qualitative research method was applied and unstructured interviews were employed through which the indispensable and paramount testimonies were acquired fastidiously. Data analysis revealed that Educational tourists are the mainstream of economic source as well as the major characterizing factor of the nature of the positive or negative social, cultural and environmental impacts in Famagusta city. The presence of educational tourists completely has changed the quality of life in Famagusta which is perceived positively by the locals. Enhancement of social activities, rejuvenating of traditions, increase of public facilities, increase of general knowledge of the habitants, enhancing the image of the TRNC is some of the positive aspects of the educational tourist impacts and on the opposite side decrease of the social ethics, commercializing of the culture, increase of the crime rate, drug use and sexual harassment are some of the negative aspects of this phenomena in Famagusta indigenous. Keywords: Educational Tourism, Socio-Cultural impacts, Host Community, Famagusta, TRNC

ÖZ: Turizmin ekonomi ve fiziksel çevre üzerindeki belirgin ve güçlü etkisinin yanı sıra ev sahibi toplulukların sosyo-kültürel değişimlerinde de katkıda bulunmaktadır. Turizmin ekonomik ve sosyo-kültürel açılarından en etkili parçalarından olan eğitim turizmi, dünya çapında gelişimine hızla devam etmektedir. Önceki çalışmalar, eğitim turizminin ekonomik etkisi üzerinde yoğunlaşırken ve sosyal ve kültürel etkilerine sadece değinirken; bu çalışmanın temel amacı eğitim turizminin Kuzey Kıbrıs’ta bulunan Gazimağusa şehrinde ikamet eden yerli insanlar üzerindeki uygulanabilir sosyal ve kültürel yararlarını detaylı bir biçimde incelemektir. Konuyla ilgili verileri toplamak amacıyla, nitel araştırma tekniği kullanılmış ve formatsız görüşmeler gerçekleştirilmiştir; böylelikle gerekli ve önemli ifadeler titizlikle alınabilmiştir. Veri analizi sonuçlarında, Eğitim turistlerinin Gazimağusa’daki ekonomik kaynağın temel etkeni olduğu ve Gazimağusa şehrindeki sosyal, kültürel ve doğa etkenlerinin olumsuz veya olumlu doğasının temel şekillendirici etkeni olduğu ortaya çıkmıştır. Eğitim amaçlı turistlerin varlığı, Gazimağusa’da yaşayan insanların yaşam kalitesinde, yerli halk tarafından olumlu olarak algılanan, büyük bir değişime neden olmuştur. Gazimağusa’da ikamet eden yerli insanlara gore, sosyal aktivitelerin arttırılması, geleneklerin canlandırılması, kamu tesislerinin çoğaltılması, yerli halkın genel kültürünün geliştirilmesi, KKTC’nin yurtdışındaki imajının geliştirilmesi eğitim turizminin olumlu etkilerini oluştururken; buna karşılık olarak sosyal ahlağın azalması, kültürün ticaretleştirilmesi, suç oranında bir artış görülmesi, uyuşturucu kullanımı ve cinsel taciz gibi durumlar ise eğitim turizminin olumsuz etkilerini oluşturmaktadır. Anahtar Kelimeler: Eğitim Türizmi, Sosyo-Kültürel etkileri, Evsahibi Topluluk, Gazimağusa, KKTC
Master of Science in Tourism Management. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Tourism, 2013. Supervisor: Assist. Prof. Dr. İlkay Yorgancı.
Keywords: Tourism; Tourism - Educational Tourism - Famagusta (Cyprus, North); Educational Tourism; Socio-Cultural impacts; Host Community; Famagusta; TRNC